Water associated zero maze: a novel rat test for long term traumatic re-experiencing - Ritov, Gilad; Richter-Levin, Gal (Frontiers in Behavioral Neuroscience, 2014)
Often, freezing and startle behaviors in the context of a previously experienced stress are taken as an indication of posttraumatic stress disorder (PTSD)-like symptoms in rats. However, PTSD is characterized by large individual variations of symptoms. In order to take into consideration the complex and long term distinctive variations in effects of trauma exposure additional behavioral measures are required. The current study used a novel behavioral test, the Water Associated Zero Maze (WAZM). This test was planned to enable a formation of an association between the context of the maze and an underwater trauma or swim stress in order to examine the impact of exposure to the context which immediately precedes a stressful or a traumatic experience on rat's complex behavior. Rats were exposed to the WAZM and immediately after to an underwater trauma or short swim. One month later rats were re-exposed to the context of the WAZM while their behavior was video recorded. Furthermore, c-Fos expression in the amygdala was measured 90 min after this exposure. The results of the current study indicate that the WAZM can be used to discern behavioral changes measured a long time after the actual traumatic or stressful events. Furthermore, the behavioral changes detected were accompanied by changes of c-Fos expression in the amygdala of exposed rats. We suggest that the WAZM can be used to model traumatic memories re-experiencing in rodent models of human stress-related pathologies such as PTSD.